Food microbiology - Adams, Martin R.; Moss, M. O. (Cambridge, U.K. : RSC Publishing, 2008)
"This widely acclaimed text covers the whole field of modern food microbiology. Now is in its third edition, it has been thoroughly revised and updated to include the most recent developments in the field." "It covers the three main aspects of the interaction between microorganisms and food - spoilage, food borne illness and fermentation -and the positive and negative features that result. It discusses the factors affecting the presence of micro-organisms in foods and their capacity to survive and grow. Also included are recent developments in procedures used to assay and control the microbiological quality of food and protect public health." "The book is a thorough and accessible account designed for students in the biological sciences, biotechnology and food sciences. It will also be valuable to researchers, teachers and practising food microbiologists."--BOOK JACKET
1. The scope of food microbiology -- 2. Micro-organisms and food materials -- 3. Factors affecting the growth and survival of micro-organisms in foods -- 4. The microbiology of food preservation -- 5. Microbiology of primary food commodities -- 6. Food microbiology and public health -- 7. Bacterial agents of foodborne illness -- 8. Non-bacterial agents of foodborne illness -- 9. Fermented and microbial foods -- 10. Methods for the microbiological examination of foods -- 11. Controlling the microbiological quality of foods
Includes bibliographical references (p. [440]-446) and index
Keywords: Food -- Microbiology; Food of animal origin -- Safety measures